PELAKSANAAN PROYEK INDIVIDU UNTUK MENGUKUR KEMAMPUAN BELAJAR SISWA KELAS VI SDIT - Kinanti, Afra Diar (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
Teachers serve as facilitators in developing students' abilities. Therefore, it is essential for teachers to design meaningful learning experiences. The meaningfulness of learning depends greatly on the learning methods used. Learning that involves doing and communicating can achieve up to 90% effectiveness. One approach that emphasizes both character development and active student participation in the learning process is Project-Based Learning (PBL). Project-based learning can be implemented either in groups or individually. Projects carried out individually are referred to as individual projects. Individual projects offer a learning strategy that provides students the opportunity to independently explore their areas of interest in greater depth. This study aims to examine the management of individual project implementation among sixth-grade students at SDIT Bening as a means to assess their learning abilities. The research employed a qualitative method. The findings reveal that: (1) individual projects can be implemented to enhance students’ learning abilities, and (2) individual projects can serve as a tool to assess students’ learning abilities. ABSTRAKGuru adalah fasilitator dalam mengembangkan kemampuan peserta didik. Maka dari itu, guru perlu menyusun pembelajaran yang bermakna. Kebermaknaan belajar tergantung dari cara belajar. Kebermaknaan belajar dengan melakukan dan mengomunikasikan bisa mencapai 90%. Salah satu pendekatan yang menekankan pada karakter juga peran aktif peserta didik dalam proses belajar yaitu Project Based Learing (PBL) atau pembelajaran berbasis proyek. Pembelajaran proyek dapat dilakukan secara kelompok maupun individu. Proyek yang dilakukan oleh individu disebut proyek individu. Proyek individu menjadi salah satu strategi pembelajaran yang memberikan kesempatan kepada setiap peserta didik untuk mengeksplorasi bidang yang diminati lebih mendalam secara mandiri. Penelitian ini dilakukan untuk mengetahui manajemen pelaksanaan proyek individu siswa kelas VI SDIT Bening untuk mengukur kemampuan belajar siswa. Penelitian menggunakan metode kualitatif. Hasil penilitian yang ditemukan yaitu: 1) proyek individu dapat dilaksanakan untuk meningkatkan kemampuan belajar siswa, 2) proyek individu dapat dilaksanakan untuk mengukur kemampuan belajar siswa.